KONSEP PEMBANGUNAN EKONOMI ISLAM - Mth, Asmuni (Al-Mawarid Jurnal Hukum Islam, 2003)
The development of economy always emphasizes on the growth aspect without considering moral values prevailing in the society. Looking at the fact, then, Islamic economists conceptualize that the development is focused not only on the material aspect, but also on the moral values. The first is necessary to fulfil the ideal needs of the society, which is namely al-had al-kifayah. On the other hand, the later -moral values aspect- is developed in order to achieve the Blessing of Allah Al-Mighty. In addition, the development of economy is not only to provide higher growth only, but it should also be in line with the justice of the distribution. Thus, the economic growth which is relatively less, is considered good if it is followed by the justice of the distribution. Of all, however, both qualitative and quantitative standards of the economic growth is still ignored by the thoughts of Islamic economists.